2011
DOI: 10.1055/s-0031-1300425
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Erdosteine and Its Metabolites on Bacterial Adhesiveness

Abstract: Summary Erdosteine (CAS 84611-23-4) is administered as a mucolytic drug in patients with pulmonary disorders who suffer from a thickening of bronchial mucus with altered physico-chemical characteristics. Erdosteine itself does not have a free thiol group but its metabolization produces active metabolites with a -SH group that is capable of breaking disulfide bonds of mucins and improving the mucociliary clearance of the airways, and thus reproducing the effects of the class of mucoactive drugs having a thiol g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 25 publications
(33 reference statements)
0
6
0
1
Order By: Relevance
“…Similarly, less risk for exacerbations of chronic bronchitis or chronic obstructive pulmonary disease (COPD) has been recently confirmed in patients taking mucolytics probably due to reduced mucus viscosity making it easier to expectorate (Poole et al, 2019). Mucolytics provide also additional direct cilio-stimulatory and bronchodilator effects without impact on the cough sensitivity, anti-inflammatory (Pappova et al, 2017;Frañováet al, 2019), antioxidant (Miyake et al, 1999) or immunomodulatory properties, in addition to the ability to reduce bacterial adhesiveness (Braga et al, 1999, Pappová et al, 2018.…”
Section: Cilia In Mucociliary Clearancementioning
confidence: 99%
“…Similarly, less risk for exacerbations of chronic bronchitis or chronic obstructive pulmonary disease (COPD) has been recently confirmed in patients taking mucolytics probably due to reduced mucus viscosity making it easier to expectorate (Poole et al, 2019). Mucolytics provide also additional direct cilio-stimulatory and bronchodilator effects without impact on the cough sensitivity, anti-inflammatory (Pappova et al, 2017;Frañováet al, 2019), antioxidant (Miyake et al, 1999) or immunomodulatory properties, in addition to the ability to reduce bacterial adhesiveness (Braga et al, 1999, Pappová et al, 2018.…”
Section: Cilia In Mucociliary Clearancementioning
confidence: 99%
“…The effect of Er and Met I on bacterial adhesion, mature biofilm and biofilm dispersal, by setting up a laboratory-scale model system simulating conditions encountered in vivo. Pharmacological concentrations close to the plasma peak value obtained after oral administration and previously used by Braga et al [ 26 ] has been used. Additionally, the impact of ROS on biofilm formation was measured.…”
Section: Discussionmentioning
confidence: 99%
“…Scientific evidence showed that thiol-based drugs can reduce bacterial adhesion to the respiratory epithelial cell surface, inhibiting biofilm formation and improving the efficacy of antibiotic therapy [ 25 ]. It has been reported that 2.5, 5 and 10 mg/L of Met I acts at a fimbrial level, by reducing both S. aureus and Escherichia coli adhesiveness to human mucosal epithelial cells that is the first step in the development of respiratory tract infections [ 26 ]. Braga et al [ 26 ] suggested that Er and Met I exert their anti-adhesion activity by inducing a stereochemical conformational change of the pilin molecules that impedes their binding to the receptors of human cells.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The therapeutic benefit of thiols is not limited to their mucolytic effect. Several preclinical studies and data collected from humans have shown the ability of these agents to interfere with inflammatory pathways 5,9,10 , modulate human bronchial tone 11 , reduce bacterial adhesion to the surface of respiratory epithelial cells [12][13][14] , and inhibit biofilm formation or cause their rupture, thus improving the efficacy of antibiotic therapy 12 . However, not all of these additional actions have been documented for each of the three thiols 2 .…”
Section: Thiol-based Mucolyticsmentioning
confidence: 99%